Pengaruh Kurikulum Merdeka terhadap Pendidikan Karakter di Sekolah Dasar - Juliana Margareta Sumilat; Lady Carolina Pangalo (Departement of Mathematics Education, 2024)
Strengthening the character of the students is the outcame of the educational process that is implemented and plays a role in the advancement of the civilization in the country. The Merdeka curriculum ensures that students are not only educated intellectually, but also have a good character. The aim of this research is to know the impact of the application of independent curricula in primary school on character education.This research method involves library research using a library survey as a data collection technique. For researchers' reference, data is taken from various journals or previous research. The results of this study explained that character education played an important role in drawing students who were not only cognitive intelligentsia but also noble morality. On the other hand, his research suggests that enhanced character education is combined with several other subjects, including good moral knowledge, good emotions or good love, good behavior. (moral behavior). Therefore, the application of the independent learning curriculum is very important in preparing Indonesia for the era of globalization and in educating the children of the nation who have high character values, values of nationalism, where in the Merdeka Curriculum one of the objectives is to develop character through the concept of student profile Pancasila that exists in the curricula.